O multilateralismo: conceitos e práticas no século XXI - Sandra Dias Fernandes (Investigação, 2019)
This book addresses the conceptualisation and practice of multilateralism since the end of World War II and the current challenges facing it. It introduces a dialogic reading of multilateralism based on the reflection-action nexus and presents a set of contributions addressing the main actors and themes of multilateral practices. Building on the United Nations system and the promotion of international peace and security, other themes are also developed, including the European Union's relations with Russia and the African continent, the foreign policies of the US, Brazil and Portugal, as well as the new Asian economic order led by China. This work is a useful tool for research and teaching of International Relations in Portuguese language.